2016
DOI: 10.2146/ajhp160072
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a multidisciplinary pharmacogenomics clinic in a community health system

Abstract: A multidisciplinary clinic providing genotyping and related services can facilitate the integration of pharmacogenomics into clinical care and meet the needs of early adopters of precision medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 72 publications
2
100
0
Order By: Relevance
“…According to another study, physicians found utility in providing PGx testing to improve patient outcomes by individualizing treatment to guide medication decisions and to decrease time and cost for maximizing the benefits of needed medications [35]. Utilizing PGx testing in order to avoid side effects from medication and improve medication effectiveness have been proposed as benefits in other studies as well [5,17,20,[35][36][37].…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 99%
See 1 more Smart Citation
“…According to another study, physicians found utility in providing PGx testing to improve patient outcomes by individualizing treatment to guide medication decisions and to decrease time and cost for maximizing the benefits of needed medications [35]. Utilizing PGx testing in order to avoid side effects from medication and improve medication effectiveness have been proposed as benefits in other studies as well [5,17,20,[35][36][37].…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 99%
“…Implementation of PGx has been attempted in a variety of settings and using various methods. A multidisciplinary clinic approach utilized medical geneticists, pharmacists, an advanced practice nurse and genetic counselors [17]. Although this model provides the patient a thorough evaluation of the pharmacogenetic variants they are found to carry, such effort lacks scalability to be an efficient sole implementation effort for a health system.…”
Section: Introductionmentioning
confidence: 99%
“…(1014) In many ways, these community-based care models have taken the essential elements needed for pharmacogenetic testing identified in early clinical academic models and developed pragmatic solutions individualized to their own practice environment to overcome implementation barriers. Such adaptations include outsourcing some aspects of preemptive, panel-based pharmacogenetic testing and interpretation to a commercial laboratory that provides evidence interpretation, recommendations for clinical decision making, an external platform to store test results, and capitated patient payment models to encourage test uptake (11,14); prescriber partnership with trained physician extenders (e.g., nurses, genetic counselors, pharmacists) to communicate test results to patients (1214); exploration of patient self-pay models to overcome the immediate cost barrier of preemptive testing (10,14); increasing patient access by providing pharmacogenetic testing in nontraditional settings, such as community-based pharmacies and community hospitals (10, 12, 14); and leveraging technological advances, such as the ability to link test results to an evidence-based prescribing decision support system for clinicians. (11,14)…”
Section: The Changing Landscape Of Preemptive Panel-based Pharmacogementioning
confidence: 99%
“…While our study focused on the specific application of CYP2C19 genotype-guided therapy for clopidogrel therapy, efforts to incorporate genetics into medication prescribing and management are becoming more common 32. The uptake in pharmacogenetics in clinical settings is being driven by the availability of evidence-based guidelines for valid and clinically actionable drug-gene pairs, as well as the incorporation of genetic information in EHR and development of associated clinical decision support tools 33.…”
Section: Discussionmentioning
confidence: 99%